The Effect of HOTS Learning and Self Regulation on Students Cognitive Ability at SMK Negeri 1 Modoinding - Tamboto, Henry J.D.; Tiwow, Gilly M.; Evinita, Lenny Leorina (Asia Pacific Journal of Management and Education (APJME), 2022)
To realize the learning in the 21st century, teachers must have good process skills in learning. The development of HOTS learning is one of the programs developed by the government in an effort to improve the quality of learning and the quality of graduates. The purpose of this study was to determine the effect of HOTS learning and student self-regulation on the cognitive abilities of students of SMK Negeri 1 Modoinding. This study used a survey method and a sample of 125 students.  Collecting data using a questionnaire (questionnaire) and documentation techniques. The results of the study were analyzed using statistical regression tests. The results showed that HOTS learning had an effect on students' cognitive abilities. Students' self-regulation affects students' cognitive abilities and HOTS learning and students' self-regulation simultaneously affects the cognitive abilities of students of SMK Negeri 1 Modoinding.